FACTORS AFFECTING ENTREPRENEURIAL INTENTION AMONG FINAL YEAR UNDERGRADUATES: THE MODERATING ROLE OF GENDER - PERERA, M.P.S.R; UDAYANGA, M.V.S.S. (My University, 2017)
Entrepreneurship has been identified as the engine of long-term economic growth of a nation as it is a leading factor in achieving economic growth, high employment, strong job creation, and positive social development. It drives and shapes innovation, speeding up structural changes in the economy. Small and Medium Enterprises are the breeding ground for entrepreneurs to set up their ventures for many reasons. However, the recent statistics depict that the failure rate of SMEs are very high. As a result, a less number of successful entrepreneurs can be seen. Therefore, it is a timely need to promote entrepreneurship among individuals. Thus, entrepreneurial intention of individuals is of critical importance in this regard.The main objective of this study is to find out the factors that affect entrepreneurial intention among the final year undergraduates of the University of Sri Jayewardenepura, Sri Lanka. The study involves three factors, that come under the Theory of Planned Behaviour i.e. attitudes, subjective norms and perceived behavioural control, which affect the entrepreneurial intention of individuals.Also, the study attempts to assess the effect of gender on the said factors. A total of 344 students from four faculties of the University of Sri Jayewardenepura participated in this study by responding to the structured questionnaire. Structural Equation Modelling was used to analyse the data using Smart PLS. Findings of the study revealed that attitudes and perceived behavioural control is positively related with entrepreneurial intention while subjective norms are negatively related with the same. The study also revealed that, only the relationship between subjective norms and entrepreneurial intention is moderated by gender. Further, it was found that, males are more responsive to the subjective norms than the female counterparts.